2016
DOI: 10.3109/07420528.2016.1152976
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circadian-related gene expression profiles in entrained breast cancer cell lines

Abstract: Cancer cells have broken circadian clocks when compared to their normal tissue counterparts. Moreover, it has been shown in breast cancer that disruption of common circadian oscillations is associated with a more negative prognosis. Numerous studies, focused on canonical circadian genes in breast cancer cell lines, have suggested that there are no mRNA circadian-like oscillations. Nevertheless, cancer cell lines have not been extensively characterized and it is unknown to what extent the circadian oscillations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 24 publications
6
41
0
1
Order By: Relevance
“…However, cultured human mammary epithelial cells maintain an inner circadian clocks. 22,41,42 Using luciferase reporter technology, our results revealed also serum shock induced the rhythmical expression of Bmal1 promotor in non-tumorigenic epithelial cell line MCF-10A, supporting it was endowed with functional circadian clocks. But ER C MCF-7 cell did not display an evident circadian oscillations of core clock genes expression under the examination of luciferase reporter technology, qRT-PCR and western-blot.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…However, cultured human mammary epithelial cells maintain an inner circadian clocks. 22,41,42 Using luciferase reporter technology, our results revealed also serum shock induced the rhythmical expression of Bmal1 promotor in non-tumorigenic epithelial cell line MCF-10A, supporting it was endowed with functional circadian clocks. But ER C MCF-7 cell did not display an evident circadian oscillations of core clock genes expression under the examination of luciferase reporter technology, qRT-PCR and western-blot.…”
Section: Discussionsupporting
confidence: 51%
“…[30][31][32][33][34] However, circadian rhythms are often altered in breast cancer patients [35][36][37] as well as in breast tumors and breast cancer cells lines. 22,[38][39][40][41][42] Alterations and desynchronization of molecular clock machinery on genetic and epigenetic level were observed in more aggressive breast cancer and those lacking estrogen receptor. Numerous studies have suggested that there are no mRNA circadian-like oscillations of canonical circadian genes in many breast cancer cell lines, either in ER C cells (such as MCF-7 or T47D) or in ERcells (such as HS578T and MDA-MB231).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oscillations of these and ancillary circadian genes have been found to be arrhythmic/absent in several disease models and tissues, including peripheral blood mononuclear cells from chronic myeloid leukemia, 2 colorectal liver metastases, 3 and prostate 4 and breast cancer cell lines. [5][6][7][8] In most of these cases, RT-qPCR, western blots, and immunohistochemistry were used to evaluate circadian changes. These assays result in less-detailed oscillation assessments because sampling frequency is typically 4-6 h and the experiment covers ~48 h; more time-points and collection over a longer duration are difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies revealed that core clock gene transcripts are present, but do not oscillate in breast cancer cell lines. [6][7][8][9][10] As examples, in work using MCF7 and MDA-MB-231 (among other breast cancer) cells, RT-qPCR and DNA/miRNA microarray data show that core circadian genes BMAL1 and PER2 lack rhythmic oscillations, although some clock controlled genes (CCGs) and miRNAs are rhythmic. 6,8 Another study in MCF7 cells indicated that upon synchronization, some core clock genes…”
Section: Introductionmentioning
confidence: 99%